The impact of transitory climate risk on firm valuation and financial institutions: A~stress test approach - Alexander Schult; Sebastian Müller; Gunther Friedl; Alberto Spagnoli (Schmalenbach Journal of Business Research (SBUR), 2024)
Addressing recent calls by European regulatory and supervisory authorities, we develop a~new bottom-up climate risk assessment method to examine the resilience of the European banking industry regarding transitory climate risks. We illustrate our approach by estimating the impact of a~50-100 EUR carbon tax per tCO2 equivalent on the valuation and default risk of STOXX Europe 600 firms. For about 5% of the sample firms, we find asset devaluation shocks larger than 30% and for about 16% of the firms probabilities of default (PDs) dropping below investment-grade level of 3%. At the sector level, our results yield asset devaluations shocks of 15-36% and new PDs of 5-34% for the six most affected sectors. Running a~stress test on credit risk based on these results, we find a~decrease in capital ratios between -1.2 and -1.6 percentage points for key regulatory capital ratios in the most adverse scenario while only addressing 36% of the bank's total risk-weighted assets. Our analysis sheds light on the substantial transitory climate risk for asset portfolios of banks and contributes to the pressing question how to integrate climate risk into risk management and regulation of financial institutions.
Keywords: G21; G28; G32; 650; Climate Stress Test; Climate Transition Risk; ESG; Financial Stability; Risk Management